Media Pembelajaran Interaktif Pendidikan Agama Islam Berbasis Augmented Reality - Lutfiana Romadan (UM Purwokerto Press, 2023)
Technological developments that are increasingly developing are increasingly advanced and rapid. This makes education a new challenge in the learning process, especially in the subject of Islamic Religious Education. So that in the PAI learning process there needs to be innovation in the media used in the learning process. Augmented Reality is a medium that is quite interesting in the PAI learning process. In addition to being more interactive, augmented reality has the ability to combine 2D object features and 3D objects in real time. The method used in this study is research and development with the ADDIE development method (analysis, design, development, implementation and evaluation. Data collection techniques use qualitative and quantitative data collection, qualitative data is generated from interviews, criticism and suggestions, while quantitative data is generated from a questionnaire which is then converted to qualitative data with a Likert scale. The workings of augmented reality applications are observation and reconstruction. At the beginning, the marker is detected by the smartphone camera. The detection model includes different algorithms such as edge detection or target image processing algorithms (Yilmaz, 2016) The image or object obtained from the detection process is used to reconstruct a real-time coordinate system Interactive learning media for Islamic Religious Education based on augmented reality can increase students' interest in learning because by using this learning media students will be it works with real time features and it's easy to learn Islamic Religious Education material.